Quality of life of patients with cervicogenic headaches = Jakość życia pacjentów z bólem głowy pochodzenia szyjnego - Janusz Kocjan (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Quality of life of patients with cervicogenic headaches = Jakość życia pacjentów z bólem głowy pochodzenia szyjnego. Journal of Education, Health and Sport. 2016;6(1):138-146. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45134